2023
DOI: 10.3390/polym15020397
|View full text |Cite
|
Sign up to set email alerts
|

Color Assessment of Feldspathic Ceramic with Two Different Thicknesses, Using Multiple Polymeric Cements

Abstract: The purpose of this study was to evaluate the color changes of feldspathic ceramics CEREC Blocs (Dentsply Sirona, Milford, DE, USA) when cemented with different luting agents, while varying the ceramic thickness. Seventy ceramic discs of feldspathic ceramic (A2 shade) were obtained with 0.5 and 0.8 mm thicknesses. Seventy composite discs (A3 shade) 1 mm in thickness were used as substrates. After being polished and conditioned, the ceramic and composite discs were cemented with different resin cements and a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…However, the ΔE values between the try-in pastes and resin cements have been found to increase with decreasing ceramic thickness, suggesting a decline in compatibility. Gomes et al 38 used 0.5 mm and 0.8 mm thick feldspathic ceramic veneers and reported that ceramic thicknesses affect the ultimate color of the restoration and that using thin ceramics has a significant effect on the result. Ayata et al 39 reported that the thickness of the veneer material used was more effective on the color masking of the final restoration than the tooth color and the translucency value of the material.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ΔE values between the try-in pastes and resin cements have been found to increase with decreasing ceramic thickness, suggesting a decline in compatibility. Gomes et al 38 used 0.5 mm and 0.8 mm thick feldspathic ceramic veneers and reported that ceramic thicknesses affect the ultimate color of the restoration and that using thin ceramics has a significant effect on the result. Ayata et al 39 reported that the thickness of the veneer material used was more effective on the color masking of the final restoration than the tooth color and the translucency value of the material.…”
Section: Discussionmentioning
confidence: 99%
“…Visual technique was not considered a precise method because of the distinction in color perception 19) . Whereas instrumental technique is a more reliable method for the color assessment 20) , which can be performed using image analysis with dental photography or digital shade taking devices such as colorimeter and spectrophotometry. Image analysis [21][22][23] and spectrophotometric analysis [20][21][22][23][24] techniques have been used in several studies previously.…”
Section: Discussionmentioning
confidence: 99%
“…There have been developments in dental ceramics that extend to all-ceramic restorations, which become the material of choice when aesthetics are crucial since they successfully mimic the visual characteristics of the tooth substance [2][3][4]. It combines strength and esthetics for acceptable and durable dental restorations [5]. There is also development in dental ceramic fabrication techniques, which include conventional condensation methods, heat pressing, subtractive manufacturing by computer-aided design, computer-aided manufacturing (CAD-CAM), and additive manufacturing by 3-D printing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are situations where ceramo-metallic restoration is recommended, such as severe bruxism, moderate gingival inflammation, high caries rates, and poor oral hygiene [7]. Shade matching in ceramo-metallic restorations is difficult because of the metal substructure [5]. In addition, the ceramic veneer overlying the metal substructure is usually built by the conventional condensation method, which mainly depends on the technician's manipulative variables, where the porcelain powders are mixed with liquid and compacted over the metal substructure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation